2000
DOI: 10.1161/01.atv.20.8.1903
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Localization of the NAD(P)H Oxidase Components gp91- phox and p22- phox in Endothelial Cells

Abstract: Abstract-The production of reactive oxygen species (ROS) within endothelial cells may have several effects, including alterations in the activity of paracrine factors, gene expression, apoptosis, and cellular injury. Recent studies indicate that a phagocyte-type NAD(P)H oxidase is a major source of endothelial ROS. In contrast to the high-output phagocytic oxidase, the endothelial enzyme has much lower biochemical activity and a different substrate specificity (NADHϾNADPH). In the present study, we (1) cloned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(160 citation statements)
references
References 56 publications
7
150
1
2
Order By: Relevance
“…Indeed, increases in overall NAD(P)H oxidase activity and O 2 -production as well as mRNA and protein expressions of p22-phox, a membrane-bound component of NAD(P)H oxidase system, have been demonstrated in proliferating compared to resting CMEC. NAD(P)H oxidase is a multicomponent enzyme system that consists of several cytsosolic subunits including p47-phox and p67-phox as well as two membrane-bound components namely p22-phox and gp91-phox that make up cytochrome b 558 [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, increases in overall NAD(P)H oxidase activity and O 2 -production as well as mRNA and protein expressions of p22-phox, a membrane-bound component of NAD(P)H oxidase system, have been demonstrated in proliferating compared to resting CMEC. NAD(P)H oxidase is a multicomponent enzyme system that consists of several cytsosolic subunits including p47-phox and p67-phox as well as two membrane-bound components namely p22-phox and gp91-phox that make up cytochrome b 558 [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Since cytochrome b 558 accounts for enzyme activity and stability as a whole, it is assumed that the alteration(s) occur in the expression of one subunit is/are reflective of similar changes in the other [12]. Hence, the current study solely concentrated on the changes in mRNA and protein expression of p22-phox subunit that is expressed in abundance in CMEC [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assembled oxidase can then use cytosolic NADPH to reduce extracellular O 2 to O :¡ 2 . Several studies showed that the mitogenic response of nonphagocytic cells requires the production of ROS by an NADPH oxidase (7,16,17 ) and similar or identical phox components have been found in a variety of cell types, including smooth muscle cells, broblasts, endothelial cells, and others, either at the RNA or protein levels (18)(19)(20). Homologues of gp91 phox , the catalytic moiety of the phagocyte NADPH oxidase, have been identi ed and are referred to as NOX.…”
Section: Sources Of Rosmentioning
confidence: 99%